High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

How to predict response to anti-tumour necrosis factor agents in inflammatory bowel disease. - Naviglio, Samuele; Giuffrida, Paolo; Stocco, Gabriele; Lenti, Marco Vincenzo; Ventura, Alessandro; Corazza, Gino Roberto; Di Sabatino, Antonio (Expert Rev Gastroenterol Hepatol, 2018)
INTRODUCTION: Anti-tumor necrosis factor (TNF) agents have changed the therapeutic approach to inflammatory bowel disease (IBD). However, a considerable proportion of patients either do not primarily respond or lose response to treatment. Despite the long-standing experience in the use of these drugs, still there is the need of identifying the possible predictors of efficacy. Areas covered: We critically review the current knowledge on predictors of response to anti-TNF therapy - both those available in clinical practice and those still under investigation. Multiple factors are involved in treatment success, including disease phenotype and severity, adherence to medications, and pharmacogenomic, pharmacokinetic, and immunologic factors. Literature search was conducted in PubMed using keywords 'inflammatory bowel disease,' 'Crohn's disease,' and 'ulcerative colitis,' matched with 'antitumor necrosis factor,' 'biologic therapy,' 'clinical response,' 'predictors,' and 'efficacy,' Relevant articles were selected for review. Expert commentary: While the role of several factors in clinical practice is clearly established, other investigational markers have been proposed, mostly in small studies, yet for many of them little external validation exists. Therapeutic drug monitoring is emerging as a pivotal strategy to guide decisions in clinical practice. In the near future, novel markers could improve our ability to direct treatment and personalize therapy.
Keywords: Antibodies, Monoclonal; Biological Therapy; Gastrointestinal Agents; Humans; Inflammatory Bowel Diseases; Patient Selection; Prognosis; Treatment Outcome; Tumor Necrosis Factor-alpha

Human beta defensin-1 is involved in the susceptibility to adeno-tonsillar hypertrophy. - Zupin, Luisa; Celsi, Fulvio; Bresciani, Martina; Orzan, Eva; Grasso, Domenico Leonardo; Crovella, Sergio (Int J Pediatr Otorhinolaryngol, 2018)
INTRODUCTION: Innate immunity molecules are known to play a pivotal role in the homeostasis of the oral mucosa, permitting the presence of commensal microflora and, at the same time, providing a first line of defense against pathogens attempting to invade the oral cavity. Tonsils represent the local immune tissue in oral cavity, being able to provide a non-specific response to pathogens; however, in the presence of microbes or foreign materials present in the mouth tonsils could became infected and develop chronic inflammation, thus leading to hypertrophy. The etiology of the disease is multifactorial depending upon environmental and host factors, the latter including molecules of mucosal innate immunity. METHODS: Ninety-five children with adeno-tonsillar hypertrophy subjected to adeno-tonsillectomy were recruited at the pediatric otorhinolaryngology service of the Institute for Maternal and Child Health IRCCS Burlo Garofolo, Trieste (Italy). The specimen discarded from the surgery were used for genomic DNA extraction and genotyping, for mRNA extraction and gene expression analysis, finally the samples were cut and used to prepare slides to perform immunohistochemistry. RESULTS: Functional polymorphisms within DEFB1 gene, encoding the human beta defensin-1 (hBD-1), were analyzed finding association between DEFB1 rare haplotypes and susceptibility to adeno-tonsillar hypertrophy. DEFB1 mRNA expression was detected in the tonsils and the hBD-1 protein was localized at the epithelia of tonsils mainly in the proximity of the basal lamina. CONCLUSION: Our findings lead us to hypothesize an involvement of hBD-1 mediated innate immunity in the modulation of the susceptibility towards adeno-tonsillar hypertrophy development.
Keywords: Adenoidectomy; Adenoids; Adolescent; beta-Defensins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Hypertrophy; Immunity, Innate; Immunohistochemistry; Italy; Male; Palatine Tonsil; Tonsillectomy

Hypomorphic FANCA mutations correlate with mild mitochondrial and clinical phenotype in Fanconi anemia. - Bottega, Roberta; Nicchia, Elena; Cappelli, Enrico; Ravera, Silvia; De Rocco, Daniela; Faleschini, Michela; Corsolini, Fabio; Pierri, Filomena; Calvillo, Michaela; Russo, Giovanna; Casazza, Gabriella; Ramenghi, Ugo; et al. (Haematologica, 2018)
Fanconi anemia is a rare disease characterized by congenital malformations, aplastic anemia, and predisposition to cancer. Despite the consolidated role of the Fanconi anemia proteins in DNA repair, their involvement in mitochondrial function is emerging. The purpose of this work was to assess whether the mitochondrial phenotype, independent of genomic integrity, could correlate with patient phenotype. We evaluated mitochondrial and clinical features of 11 affected individuals homozygous or compound heterozygous for p.His913Pro and p.Arg951Gln/Trp, the two residues of FANCA that are more frequently affected in our cohort of patients. Although p.His913Pro and p.Arg951Gln proteins are stably expressed in cytoplasm, they are unable to migrate in the nucleus, preventing cells from repairing DNA. In these cells, the electron transfer between respiring complex I-III is reduced and the ATP/AMP ratio is impaired with defective ATP production and AMP accumulation. These activities are intermediate between those observed in wild-type and FANCA-/- cells, suggesting that the variants at residues His913 and Arg951 are hypomorphic mutations. Consistent with these findings, the clinical phenotype of most of the patients carrying these mutations is mild. These data further support the recent finding that the Fanconi anemia proteins play a role in mitochondria, and open up possibilities for genotype/phenotype studies based on novel mitochondrial criteria.

Higher growth, fat and fat-free masses correlate with larger cerebellar volumes in preterm infants at term. - Paviotti, Giulia; De Cunto, Angela; Zennaro, Floriana; Boz, Giulia; Travan, Laura; Cont, Gabriele; Bua, Jenny; Demarini, Sergio (Acta Paediatr, 2017)
AIM: Smaller cerebellar volumes in very low-birthweight (VLBW) infants at term have been related to adverse cognitive outcomes, and this study evaluated whether these volumes were associated with a growth in body composition during hospital stays. METHODS: We prospectively recruited 42 VLBW infants from an Italian neonatal unit between January 2013 and August 2015. Cerebellar volumes and body composition were measured by magnetic resonance imaging (MRI) and air-displacement plethysmography, respectively, at 40 weeks of gestational age and anthropometric and nutritional data were collected. We also included 20 term-born controls. RESULTS: The mean gestational age and birthweight of the VLBW infants were 29.4 (±1.9) weeks and 1120 (±290) g. There was a positive correlation between cerebellar volumes and daily weight gain from birth to term (R = 0.26, p = 0.001), weight (R = 0.25, p = 0.001), length (R = 0.16, p = 0.01), fat mass (R = 0.15, p = 0.01) and fat-free mass at term (R = 0.20, p = 0.003). In multiple regression analysis, daily weight gain, mechanical ventilation and postconceptional age at MRI were independently associated with cerebellar volumes. Anthropometric data and cerebellar volumes were similar between VLBW and control infants. CONCLUSION: Higher growth, higher fat mass and fat-free mass were associated with larger cerebellar volumes in VLBW infants at term.
Keywords: Body Composition; Cerebellum; Child Development; Female; Humans; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Male; Nutritional Status; Organ Size; Prospective Studies; Regression Analysis

Histoproteomic Characterization of Localized Cutaneous Amyloidosis in X-Linked Reticulate Pigmentary Disorder. - L'Imperio, Vincenzo; Bruno, Irene; Rabach, Ingrid; Smith, Andrew; Chinello, Clizia; Stella, Martina; Magni, Fulvio; Pagni, Fabio (Skin Pharmacol Physiol, 2017)
Keywords: Amyloidosis; Genetic Diseases, X-Linked; Humans; Pigmentation Disorders; Proteomics; Skin Diseases

HLA-G regulatory polymorphisms are associated with susceptibility to HCV infection. - Catamo, E; Zupin, L; Freato, N; Polesello, V; Celsi, F; Crocè, S L; Masutti, F; Pozzato, G; Segat, L; Crovella, S (HLA, 2017)
BACKGROUND: Hepatitis C virus (HCV) is able to bypass the immune system modulating innate and adaptive immune response and blocking T helper 1 (Th1) cell production. Because the human leukocyte antigen (HLA)-G molecule has immunomodulatory properties inhibiting the function and production of natural killer and cytotoxic lymphocyte T cells, as well as promoting shift from Th1 toward Th2 response, we hypothesized its involvement in susceptibility to HCV infection. MATERIALS AND METHODS: Considering that HLA-G mRNA expression has been reported to be under genetic control, an association study was conducted analyzing 800 base pairs upstream the ATG at the 5'upstream regulator region (URR) and 850 base pairs from ATG to exon 3 and the 3'untranslated region (UTR) of HLA-G gene in Italian HCV-positive patients and uninfected controls. RESULTS: Four 5'URR polymorphisms (-725C>G>T, -509C>G, -400G>A and -398G>A), 7 polymorphisms at coding region (+15G>A, +36G>A, +243G>A, insC506, 531G>C, delA615 and 685G>A), the +644G>T polymorphism, and 1 haplotype (TTGTTCCIGAC) showed different frequency distributions between HCV patients and uninfected controls. CONCLUSION: The results from our study suggest a possible involvement of HLA-G in the risk modulation toward HCV infection.
Keywords: 3' Untranslated Regions; 5' Untranslated Regions; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Exons; Female; Gene Expression; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Haplotypes; Hepacivirus; Hepatitis C; HLA-G Antigens; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk; Th1 Cells

How to monitor pregnancies complicated by fetal growth restriction and delivery before 32 weeks: post-hoc analysis of TRUFFLE study. - Ganzevoort, W; Mensing Van Charante, N; Thilaganathan, B; Prefumo, F; Arabin, B; Bilardo, C M; Brezinka, C; Derks, J B; Diemert, A; Duvekot, J J; Ferrazzi, E; Frusca, T; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: In the recent TRUFFLE study, it appeared that, in pregnancies complicated by fetal growth restriction (FGR) between 26 and 32 weeks' gestation, monitoring of the fetal ductus venosus (DV) waveform combined with computed cardiotocography (CTG) to determine timing of delivery increased the chance of infant survival without neurological impairment. However, concerns with the interpretation were raised, as DV monitoring appeared to be associated with a non-significant increase in fetal death, and some infants were delivered after 32 weeks, at which time the study protocol no longer applied. This secondary sensitivity analysis of the TRUFFLE study focuses on women who delivered before 32 completed weeks' gestation and analyzes in detail the cases of fetal death. METHODS: Monitoring data of 317 pregnancies with FGR that delivered before 32 weeks were analyzed, excluding those with absent outcome data or inevitable perinatal death. Women were allocated randomly to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate short-term variation (STV) on CTG; (2) early changes in fetal DV waveform; and (3) late changes in fetal DV waveform. Primary outcome was 2-year survival without neurological impairment. The association of the last monitoring data before delivery and infant outcome was assessed by multivariable analysis. RESULTS: Two-year survival without neurological impairment occurred more often in the two DV groups (both 83%) than in the CTG-STV group (77%), however, the difference was not statistically significant (P = 0.21). Among the surviving infants in the DV groups, 93% were free of neurological impairment vs 85% of surviving infants in the CTG-STV group (P = 0.049). All fetal deaths (n = 7) occurred in the groups with DV monitoring. Of the monitoring parameters obtained shortly before fetal death in these seven cases, an abnormal CTG was observed in only one case. Multivariable regression analysis of factors at study entry demonstrated that a later gestational age, higher estimated fetal weight-to-50 percentile ratio and lower umbilical artery pulsatility index (PI)/fetal middle cerebral artery-PI ratio were significantly associated with normal outcome. Allocation to DV monitoring had a smaller effect on outcome, but remained in the model (P < 0.1). Abnormal fetal arterial Doppler before delivery was significantly associated with adverse outcome in the CTG-STV group. In contrast, abnormal DV flow was the only monitoring parameter associated with adverse outcome in the DV groups, while fetal arterial Doppler, STV below the cut-off used in the CTG-STV group and recurrent decelerations in fetal heart rate were not. CONCLUSIONS: In accordance with the findings of the TRUFFLE study on monitoring and intervention management of very preterm FGR, we found that the proportion of infants surviving without neuroimpairment was not significantly different when the decision for delivery was based on changes in DV waveform vs reduced STV on CTG. The uneven distribution of fetal deaths towards the DV groups was probably a chance effect, and neurological outcome was better among surviving children in these groups. Before 32 weeks, delaying delivery until abnormalities in DV-PI or STV and/or recurrent decelerations in fetal heat rate occur, as defined by the study protocol, is likely to be safe and possibly benefits long-term outcome. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Central Nervous System Diseases; Child, Preschool; Female; Fetal Growth Retardation; Fetal Membranes, Premature Rupture; Gestational Age; Heart Rate, Fetal; Humans; Infant; Infant, Extremely Premature; Male; Middle Cerebral Artery; Pregnancy; Pulsatile Flow; Survival Analysis; Treatment Outcome; Ultrasonography, Prenatal; Uterine Artery

Hand-held computers can help to distract children undergoing painful venipuncture procedures. - Crevatin, Franca; Cozzi, Giorgio; Braido, Elena; Bertossa, Gabriella; Rizzitelli, Patrizia; Lionetti, Daniela; Matassi, Daniela; Calusa, Dorotea; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2016)
AIM: Needle-related procedures can be painful for children, and distraction provides ideal pain relief in blood-drawing centres. This study assessed the effectiveness of playing a computer game during venipuncture, compared with low-tech distraction by a nurse. METHODS: We conducted this prospective, randomised controlled trial at the blood-drawing centre of a tertiary-level children's hospital in Italy. Half of the 200 children played Angry Birds on a hand-held computer while the other half were distracted by a second, specifically trained nurse who sang to them, read a book, blew bubbles or played with puppets. Pain was measured using a faces pain scale for children aged 4-7 years and a numeric scale for children aged 8-13 years. RESULTS: The 200 children had a median age of eight years. Children reported significant pain in 16 cases (16%) in the hand-held computer distraction group and in 15 cases (15%) in the nurse-led low-tech distraction group (p = 0.85). The procedural success rate at the first attempt was not different in the two groups. CONCLUSION: Playing a game on a hand-held computer meant that only one in six children reported pain during venipuncture, but it was not superior to being distracted by nurses.

Hepatic Gadolinium Deposition and Reversibility after Contrast Agent-enhanced MR Imaging of Pediatric Hematopoietic Stem Cell Transplant Recipients. - Maximova, Natalia; Gregori, Massimo; Zennaro, Floriana; Sonzogni, Aurelio; Simeone, Roberto; Zanon, Davide (Radiology, 2016)
Purpose To determine if hepatic gadolinium deposition occurs in pediatric patients with iron overload but normal renal and hepatic function who undergo gadolinium-based contrast agent (GBCA)-enhanced magnetic resonance (MR) imaging. Materials and Methods Design and execution of this study was approved by the Ethical Committee of Institute for Research in Maternal and Child Health Burlo Garofolo of Trieste (reference no. 1105/2015). Because of the retrospective nature of the study, the requirement to obtain informed consent was waived. Twenty-one recipients of allogeneic hematopoietic stem cell transplants who underwent GBCA-enhanced MR imaging for suspected infection or relapse followed by liver biopsy comprised the study group. The number of GBCA-enhanced MR examinations and cumulative gadolinium dose for each patient was analyzed by comparing liver histologic analysis and iron and gadolinium liver concentration (GLC). Eight patients had siderosis and underwent chelation therapy. The study group was compared with four control patients who were never exposed to GBCA. Statistical analysis was performed with Spearman rank coefficient for correlation. Results All 21 patients had positive correlations between GLC and total GBCA dose (r = 0.4486; P < .05) and between GLC and liver iron concentration (r = 0.56; P < .05). Patients who underwent deferoxamine therapy had a significant reduction of GLC (from 0.64 μg/g ± 0.29 to 0.20 μg/g ± 0.17 [standard deviation]; P < .05). Conclusion In the presence of siderosis, a transmetallation mechanism may be set off between ferric ion and gadoterate meglumine. Deferoxamine appears capable of binding to gadolinium ion. Further studies of the safety of GBCAs in severe siderosis are needed. Chelation should be considered in patients with iron overload and a history of GBCA exposure. (©) RSNA, 2016.

Heterologous Expression Systems for Plant Defensin Expression: Examples of Success and Pitfalls. - Gazzaneo, Luis Rs; Pandolfi, Valesca; Jesus, André Ls; Crovella, Sergio; Benko-Iseppon, Ana M; Freitas, Antonio Carlos (Curr Protein Pept Sci, 2016)
Defensins are a superfamily of antimicrobial peptides, present in vertebrates, invertebrates, fungi and plants, suggesting that they appeared prior to the divergence in eukaryotes. The destitution of toxicity to mammalian cells of plant defensins has led to a new research ground, i.e., their potential medical use against human infectious diseases. Isolating defensins from natural sources, like plant tissues, can be time-consuming, labor intensive and usually present low yields. Strategies for large-scale production of purified active defensins have been employed using heterologous expression systems (HES) for defensin production, usually based in E. coli system. Like any other technology, HES present limitations and drawbacks demanding a careful experimental design prior the system selection. This review is proposed to discuss some of the major concerns when choosing to heterologously express plant defensins, with special attention on bacterial expression system.

Histopathological data of iron and calcium in the mouse lung after asbestos exposure. - Trevisan, Elisa; Zabucchi, Giuliano; Pascolo, Lorella; Pascotto, Ernesto; Casarsa, Claudia; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; Zweyer, Marina; Borelli, Violetta (Data Brief, 2016)
This data article contains data related to the research article entitled, "Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice" [1]. Asbestos fibers disrupt iron homeostasis in the human and mouse lung, leading to the deposition of iron (Fe) onto longer asbestos fibers which forms asbestos bodies (AB) [2]. Similar to Fe, calcium (Ca) is also deposited in the coats of the AB. This article presents data on iron and calcium in the mouse lung after asbestos exposure detected by histochemical evaluation.

HPV genotypes distribution in Chlamydia trachomatis co-infection in a large cohort of women from north-east Italy. - Seraceni, Silva; Campisciano, Giuseppina; Contini, Carlo; Comar, Manola (J Med Microbiol, 2016)
Human papillomavirus (HPV) and Chlamydia trachomatis are pathogens with oncogenic potential associated with persistent infections. Epidemiological data on C. trachomatis infection status, C. trachomatis/HPV co-infection and the relationship between HPV genotypes in Italian women are only preliminary. The aim of the present study was to characterize the relationship between HPV genotypes and C. trachomatis in an extending cohort of asymptomatic immunocompetent women from an area of north-east Italy. A retrospective study was conducted using Luminex technology on cervical swabs from asymptomatic immunocompetent women, comprising 921 attending the prevention centre for the Cervical Cancer Program and 6214 who had been referred to the Sexually Transmitted Infections Center, with clinical indications of HPV and C. trachomatis infections. A quantitative real-time PCR was performed to assess chronic C. trachomatis infection by heat-shock protein 60 (Hsp60) gene expression. The overall prevalence of the investigated pathogens was 39 % (359/921) for HPV and 4 % (251/6214) for C. trachomatis. The Hsp60 gene was detected in 57 % of the women infected with C. trachomatis. HPV co-infection was present in 58 % of C. trachomatis-infected women. A high prevalence of co-infection was found in women with chronic C. trachomatis infection (68 %, P = 0.0002), especially in women ≤ 25 years (72 %) where HPV multiple infections were found in 78 % (P = 0.022). HPV genotype distribution showed that uncommon low-risk genotypes were associated with C. trachomatis. These results indicate a high frequency of co-detection of multiple HPV genotypes in chronically infected young women and suggest that the expression of the C. trachomatis Hsp60 gene may favour HPV infection.

Handlebar injury in children: The hidden danger. - Pederiva, Federica; Guida, Edoardo; Maschio, Massimo; Rigamonti, Waifro; Gregori, Massimo; Codrich, Daniela (Surgery, 2015)

HLA-G and susceptibility to develop celiac disease. - Catamo, Eulalia; Zupin, Luisa; Segat, Ludovica; Celsi, Fulvio; Crovella, Sergio (Hum Immunol, 2015)
The Human Leukocyte Antigen-G has immunomodulatory function and its expression has been associated with several diseases. In our study we analyzed HLA-G polymorphisms in order to evaluate their possible association with susceptibility to celiac disease development. A total of 420 celiac patients and 509 controls were genotyped for HLA-G polymorphisms. We sequenced 800bp upstream the ATG codon (5' upstream regulatory region) and the whole 3' untranslated region of the HLA-G gene, whereas the ΔC deletion at exon 3 was detected by RFLP-PCR. Five polymorphisms (namely -477 C>G, -369 C>A, 14bp del/ins, 3187 A>G, 3196 C>G) and one haplotype (TCGGTACGAAITCCCGAG) were significantly more frequent in celiac patients than controls and associated with increased disease susceptibility. The 14bp I/I, 3187 G/G, 3196 G/G genotypes and TCGGTACGAAITCCCGAG haplotype, were still significantly associated with increased disease susceptibility (and in addition also the 3003 C/C genotype) when the analysis was restricted to patients and controls presenting the DQ2.5 or DQ8 HLA-DQ celiac disease risk haplotypes. Our findings indicate an association between HLA-G gene polymorphisms and susceptibility to celiac disease development, suggesting that HLA-G molecule is possibly involved in the pathogenesis of the disease.
Keywords: Adolescent; Adult; Alleles; Case-Control Studies; Celiac Disease; Child; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; HLA-DQ Antigens; HLA-G Antigens; Humans; Male; Middle Aged; Polymorphism, Genetic; Retrospective Studies

Hypoxaemia as a Mortality Risk Factor in Acute Lower Respiratory Infections in Children in Low and Middle-Income Countries: Systematic Review and Meta-Analysis. - Lazzerini, Marzia; Sonego, Michela; Pellegrin, Maria Chiara (PLoS One, 2015)
OBJECTIVE: To evaluate the association between hypoxaemia and mortality from acute lower respiratory infections (ALRI) in children in low- and middle-income countries (LMIC). DESIGN: Systematic review and meta-analysis. STUDY SELECTION: Observational studies reporting on the association between hypoxaemia and death from ALRI in children below five years in LMIC. DATA SOURCES: Medline, Embase, Global Health Library, Lilacs, and Web of Science to February 2015. RISK OF BIAS ASSESSMENT: Quality In Prognosis Studies tool with minor adaptations to assess the risk of bias; funnel plots and Egger's test to evaluate publication bias. RESULTS: Out of 11,627 papers retrieved, 18 studies from 13 countries on 20,224 children met the inclusion criteria. Twelve (66.6%) studies had either low or moderate risk of bias. Hypoxaemia defined as oxygen saturation rate (SpO2) <90% associated with significantly increased odds of death from ALRI (OR 5.47, 95% CI 3.93 to 7.63) in 12 studies on 13,936 children. An Sp02 <92% associated with a similar increased risk of mortality (OR 3.66, 95% CI 1.42 to 9.47) in 3 studies on 673 children. Sensitivity analyses (excluding studies with high risk of bias and using adjusted OR) and subgroup analyses (by: altitude, definition of ALRI, country income, HIV prevalence) did not affect results. Only one study was performed on children living at high altitude. CONCLUSIONS: The results of this review support the routine evaluation of SpO2 for identifying children with ALRI at increased risk of death. Both a Sp02 value of 92% and 90% equally identify children at increased risk of mortality. More research is needed on children living at high altitude. Policy makers in LMIC should aim at improving the regular use of pulse oximetry and the availability of oxygen in order to decrease mortality from ALRI.

Hysteroscopic chasing for endometrial cancer in a low-risk population: risks of overinvestigation. - Scrimin, Federica; Wiesenfeld, Uri; Galati, Emanuele F; Monasta, Lorenzo; Ricci, Giuseppe (Arch Gynecol Obstet, 2015)
PURPOSE: To evaluate the appropriateness of the indications for hysteroscopy done, in fertile and postmenopausal women, for the detection of endometrial cancer. METHODS: A retrospective analysis of 2673 consecutive women who underwent office hysteroscopy chasing for endometrial cancer between January 2012 and June 2014. According to their medical history only low-risk women entered the study. RESULTS: A total of 1070 patients entered the study. The main outcome measure was the appropriateness of the indications for hysteroscopy. Appropriateness was assessed on the basis of guidelines of scientific societies and histologic report. According to the algorithm developed for appropriateness, 44 % of procedures resulted in being inappropriate. In reproductive-aged women 57 % of hysteroscopies were inappropriate. In postmenopausal women inappropriate hysteroscopies were 45 %. In reproductive-aged women, the reasons for inappropriateness were: absence of abnormal uterine bleeding (AUB) or AUB without a trial of progestin therapy. In postmenopausal women, the reasons for inappropriateness were: ultrasound report of endometrial thickening or polyp without bleeding. CONCLUSIONS: Hysteroscopy is often recommended for inappropriate indications. More evidence is needed to identify the risks of overinvestigation, overdiagnosis, and related overtreatment and to better identify the threshold beyond which benefits are likely to outweigh harms.

Hematopoietic stem cell transplantation effects on spinal cord compression in Hurler. - Ferrara, Giovanna; Maximova, Natalia; Zennaro, Floriana; Gregori, Massimo; Tamaro, Paolo (Pediatr Transplant, 2014)
Hurler syndrome type 1 (MPS-1) is an autosomal recessive lysosomal disorder due to the deficiency of the enzyme alpha-L-iduronidase which is necessary for the degradation of dermatan and heparan sulfate. It is characterized by deposit of glycosaminoglycans in tissues, progressive multisystem dysfunction, and early death. HSCT for children with MPS-I is effective, resulting in increased life expectancy and improvement of clinical parameters. The spinal MRI performed on a female 10 yr old undergoing HSCT at the age of 18 months and receiving ERT revealed a considerable decrease in soft tissue around the tip of odontoid causing a significant reduction in spinal cord compression. In light of this result, we suppose that combined ERT and HSCT are successful in Hurler I disease.
Keywords: Bone Marrow Transplantation; Child; Enzyme Replacement Therapy; Female; Glycosaminoglycans; Hematopoietic Stem Cell Transplantation; Humans; Iduronidase; Magnetic Resonance Imaging; Mucopolysaccharidosis I; Odontoid Process; Spinal Cord Compression; Treatment Outcome

Hemophagocytic lymphohistiocytosis in total parenteral nutrition dependent children: description of 5 cases and practical tips for management. - Pastore, Serena; Barbieri, Francesca; Di Leo, Grazia; Valencic, Erica; Tommasini, Alberto; Ventura, Alessandro (J Pediatr Hematol Oncol, 2014)
Although total parenteral nutrition (TPN) is mandatory in children with intestinal failure, this treatment is not risk free. The main complications of TPN include catheter-related sepsis, thrombosis, hepatic cholestasis and cirrhosis, metabolic bone disease, and, rarely, reactive hemophagocytic lymphohistiocytosis (HLH). The pathogenesis of HLH in patients with TPN is not known, although some authors hypothesized that it can result from the activation of macrophages because of "fat overload." We reported 5 cases of HLH that occurred in patients with 4 different underlying disorders, all requiring TPN for a long term. In our series, an underlying immunological defect or a serious infection (sepsis) can have triggered HLH. Therefore, it could be reasonable to hypothesize that besides TPN in itself, minor immune defects and infections may act together by overcoming a threshold of immune stimulation, which ultimately leads to HLH.
Keywords: Child, Preschool; Fatty Acids; Female; Humans; Infant; Intestinal Diseases; Lymphohistiocytosis, Hemophagocytic; Male; Parenteral Nutrition, Total; Steroids; Treatment Outcome

Hereditary hearing loss: a 96 gene targeted sequencing protocol reveals novel alleles in a series of Italian and Qatari patients. - Vozzi, D; Morgan, A; Vuckovic, D; D'Eustacchio, A; Abdulhadi, K; Rubinato, E; Badii, R; Gasparini, P; Girotto, G (Gene, 2014)
Deafness is a really common disorder in humans. It can begin at any age with any degree of severity. Hereditary hearing loss is characterized by a vast genetic heterogeneity with more than 140 loci described in humans but only 65 genes so far identified. Families affected by hearing impairment would have real advantages from an early molecular diagnosis that is of primary relevance in genetic counseling. In this perspective, here we report a family-based approach employing Ion Torrent DNA sequencing technology to analyze coding and UTR regions of 96 genes related to hearing function and loss in a first series of 12 families coming from Italy and Qatar. Using this approach we were able to find the causative gene in 4 out of these 12 families (33%). In particular 5 novel alleles were identified in the following genes LOXHD1, TMPRSS3, TECTA and MYO15A already associated with hearing impairment. Our study confirms the usefulness of a targeted sequencing approach despite larger numbers are required for further validation and for defining a molecular epidemiology picture of hearing loss in these two countries.
Keywords: Alleles; Amino Acid Sequence; Carrier Proteins; Extracellular Matrix Proteins; Female; Genetic Testing; GPI-Linked Proteins; Hearing Loss; Humans; Italy; Male; Membrane Proteins; Molecular Sequence Data; Mutation; Myosins; Neoplasm Proteins; Pedigree; Qatar; Sequence Analysis, DNA; Serine Endopeptidases; Untranslated Regions

Heterogeneity of mesenchymal stromal cells in lymphoproliferative disorders. - Campioni, Diana; Voltan, Rebecca; Tisato, Veronica; Zauli, Giorgio (Front Biosci (Landmark Ed), 2014)
Accumulating evidence indicates that bone marrow microenvironment plays an important role in the pathogenesis of some myeloid and lymphoid hematological malignancies (HM). Among different environmental associated parameters, those related to functional, cytogenetic and immunological integrity of mesenchymal stromal cells (MSC) are particularly relevant. Functional alterations and immunophenotypic abnormalities have been described in MSC obtained from HM patients. These data seem to confirm the defective biological pattern of MSC especially in myeloid diseases, while MSC cytogenetic profile in HM is still an open question, because it is not clear whether BM stromal cells are "culprit or bystander" displaying or not an abnormal karyotype. Contradictory findings were reported in different HM but the functional implications of altered MSC karyotype need to be further addressed also in light of a clinical use of MSC. A "pathological" in vivo supportive function of endogenous MSC, which provide important survival and drug resistance signals to leukemic cells especially in lymphoproliferative disorders, is suggested. Thus, the mechanisms underlying these protective versus cytotoxic effects exerted by MSC on leukemic cells need further investigations.
Keywords: Humans; Immunophenotyping; Karyotyping; Lymphoproliferative Disorders; Mesenchymal Stromal Cells

High-frequency percussive ventilation as rescue treatment in severe hypoxemic respiratory failure in term neonates. - Paviotti, Giulia; Bua, Jenny; De Cunto, Angela; Travan, Laura; Demarini, Sergio (J Crit Care, 2014)
Keywords: Female; High-Frequency Ventilation; Humans; Male; Oxygen; Pulmonary Gas Exchange; Respiratory Insufficiency

HLA-B35, a common genetic trait, in a familial case of Henoch-Schoenlein purpura and Berger's disease. - Pellegrin, M C; Matarazzo, L; Neri, E; Pennesi, M; Crovella, S (Genet Mol Res, 2014)
Nephritis characterized by IgA mesangial depositions has been described both in Henoch-Schoenlein purpura (HSP) and in Berger's disease (BD), but common genetic traits are still uncertain. We report here the case of two brothers, the first affected by HSP with persistent nephritis and the second by BD, accidentally discovered as silent microhematuria 1 year after HSP onset in the first brother. HLA genotyping demonstrated the presence of HLA-B35 in both patients. Our findings reinforce the need to screen for urinary abnormalities in family members of patients affected by HSP nephritis to identify a silent IgA nephropathy.
Keywords: Adolescent; Child; Female; Genotype; Glomerulonephritis, IGA; HLA-B35 Antigen; Humans; Male; Middle Aged; Nephritis; Phenotype; Purpura, Schoenlein-Henoch

HLA-G 14 bp deletion/insertion polymorphism and mother-to-child transmission of HIV. - Segat, L; Zupin, L; Kim, H-Y; Catamo, E; Thea, D M; Kankasa, C; Aldrovandi, G M; Kuhn, L; Crovella, S (Tissue Antigens, 2014)
The human leukocyte antigen HLA-G, highly expressed at the maternal-fetal interface, has a pivotal role in mediating immune tolerance. In this study we investigated the influence of HLA-G 14 bp insertion polymorphism in human immunodeficiency virus (HIV)-1 mother-to-child HIV-1 transmission. The 14 bp insertion polymorphism was analyzed among 99 HIV-1 positive mothers and 329 infants born to HIV-positive mothers in Zambia, among whom vertical transmission status and timing had been determined. HLA-G 14 bp insertion polymorphism was detected using a custom TaqMan single nucleotide polymorphisms (SNPs) genotyping assay. Logistic regression was conducted to examine the associations between HLA-G alleles and the risk of HIV transmission. The 14 bp insertion allele was more frequent in HIV exposed-uninfected (EU) infants than in infected infants, and was associated with reduced risk of both in utero (IU) and intrapartum (IP) HIV transmission, after adjusting for maternal cluster of differentiation 4 (CD4) cell count and plasma viral load. Maternal HLA-G 14 bp insertion genotype and HLA-G concordance between mother and child were not associated with the risk of perinatal HIV transmission. The presence of the 14 bp insertion associates with protection toward IU and IP HIV infection in children from Zambia, suggesting that HLA-G could be involved in the vertical transmission of HIV.
Keywords: Adult; Alleles; Base Pairing; Child; Genotype; HIV Infections; HLA-G Antigens; Humans; INDEL Mutation; Infant; Infectious Disease Transmission, Vertical; Mothers; Polymorphism, Genetic; Young Adult

HLA-G gene polymorphisms associated with susceptibility to rheumatoid arthritis disease and its severity in Brazilian patients. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Domingues Barbosa, A; Tavares Dantas, A; de Ataíde Mariz, H; F da Rocha, L; Branco Pinto Duarte, A L; Monasta, L; Sandrin-Garcia, P; Crovella, S (Tissue Antigens, 2014)
We analyzed the possible association between human leukocyte antigen-G (HLA-G) genetic variants, supposed to regulate HLA-G expression, and the susceptibility to develop rheumatoid arthritis (RA) as well as its clinical manifestations. The 5'upstream regulatory region (5'URR) and 3'untranslated region (3'UTR) regions of the HLA-G gene were screened in 127 RA patients and 128 controls: 10 5'URR and 3 3'UTR HLA-G polymorphisms as well as two haplotypes were associated with risk for RA development, while a polymorphism in the 5'URR showed an association with the degree of disease activity. These findings, although the number of cases analyzed is limited and the P-values are modest, indicate a possible association between HLA-G gene polymorphisms and susceptibility to develop RA disease and its severity.
Keywords: 3' Untranslated Regions; 5' Flanking Region; Aged; Arthritis, Rheumatoid; Brazil; Disease Progression; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; HLA-G Antigens; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk

HPV and Chlamydia trachomatis co-detection in young asymptomatic women from high incidence area for cervical cancer. - Bellaminutti, Serena; Seraceni, Silva; De Seta, Francesco; Gheit, Tarik; Tommasino, Massimo; Comar, Manola (J Med Virol, 2014)
Chlamydia trachomatis causing chronic inflammatory diseases has investigated as possible human papillomavirus (HPV) cofactor in cervical cancer. The aim of this study is to evaluate the prevalence of Chlamydia trachomatis and HPV co-infection in different cohorts of asymptomatic women from a Northern Italy area at high incidence for cervical cancer. Cervical samples from 441 females were collected from Cervical Cancer Screening Program, Sexually Transmitted Infectious and Assisted Reproductive Technology centres. HPV and Chlamydia trachomatis were detected simultaneously and genotyped using a highly sensitive bead based assay. The overall prevalence of Chlamydia trachomatis was estimated 9.7%, in contrast with the reported national data of 2.3%, and co-infection with HPV was diagnosed in the 17% of the samples. In females ≤ 25 years of age, the infection reached a peak of 22% and co-infection with HPV of 45.8% (P < 0.001). Of note, in young females diagnosed with low grade cervical lesions, no significant difference between Chlamydia trachomatis and HPV distribution was observed, while differently, HPV co-infection was found significantly associated to the presence of intraepithelial lesions when compared to older females (20% vs. 1%; P < 0.001). In this study, the use of a high sensitive molecular technique exhibited higher analytical sensitivity than the referred assays for the diagnosis of Chlamydia trachomatis and HPV co-infection in asymptomatic females, leading to reduction of the potential to identify incorrectly the infection status. An active screening for timely treatment of Chlamydia trachomatis infection is suggested in young females to evaluate a possible decrease in incidence of pre-cancer intraepithelial lesions.
Keywords: Adolescent; Adult; Age Factors; Cervix Uteri; Chlamydia Infections; Chlamydia trachomatis; Coinfection; Female; Genotype; Humans; Incidence; Italy; Middle Aged; Papillomaviridae; Papillomavirus Infections; Prevalence; Young Adult

Human recombinant lysozyme downregulates advanced glycation endproduct-induced interleukin-6 production and release in an in-vitro model of human proximal tubular epithelial cells. - Gallo, Davide; Cocchietto, Moreno; Masat, Elisa; Agostinis, Chiara; Harei, Elisa; Veronesi, Paolo; Sava, Gianni (Exp Biol Med (Maywood), 2014)
Diabetic nephropathy is the leading cause of chronic renal disease and one of the major causes of cardiovascular mortality. Evidence suggests that its progression is due to the chronic hyperglycemia consequent to the production and accumulation of advanced glycation endproducts (AGEs). Lysozyme was shown to posses AGE-sequestering properties and the capacity to reduce the severity of the early stage manifestations of the diabetic nephropathy. This study was aimed to contribute to the understanding the molecular mechanisms of lysozyme effectiveness in the diabetic nephropathy, using an in-vitro cellular model, represented by the HK-2 cells, human proximal tubular epithelial cells. Lysozyme significantly reduced the AGE-induced IL-6 mRNA and an ELISA assay showed also a decreased release of the functional protein with a dose-dependent trend. In addition, lysozyme prevented macrophage recruitment, suggesting its capacity to elicit an anti-inflammatory action. We may conclude that the protective action of lysozyme on the nephrotoxic effects of AGE may depend, at least in part, on its ability to prevent the production and release of inflammatory mediators, such as IL-6 and to reduce macrophage recruitment in the inflammatory sites.
Keywords: Cell Line; Cell Movement; Cell Survival; Chemokine CX3CL1; Diabetic Nephropathies; Down-Regulation; Epithelial Cells; Glycosylation End Products, Advanced; Humans; Inflammation Mediators; Interleukin-18; Interleukin-6; Kidney Tubules, Proximal; Macrophage Activation; Macrophages; Muramidase; Recombinant Proteins; RNA, Messenger; Tumor Necrosis Factor-alpha; U937 Cells

Human colostrum and breast milk contain high levels of TNF-related apoptosis-inducing ligand (TRAIL). - Davanzo, Riccardo; Zauli, Giorgio; Monasta, Lorenzo; Vecchi Brumatti, Liza; Abate, Maria Valentina; Ventura, Giovanna; Rimondi, Erika; Secchiero, Paola; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: TNF-related apoptosis inducing ligand (TRAIL) is a pleiotropic cytokine, which plays a key role in the immune system as well as in controlling the balance of apoptosis and proliferation in various organs and tissues. OBJECTIVE: To investigate the presence and levels of soluble TRAIL in human colostrum and milk. METHODS: The levels of soluble human TRAIL were measured in human colostrum (day 2 after delivery) and breast milk (day 5 after delivery). The presence of TRAIL was also measured in infant formula. RESULTS: Levels of soluble TRAIL in the colostrum and mature human milk were, respectively, at least 400 and 100 fold higher than those detected in human serum. No TRAIL was detected in formula. CONCLUSION: Human soluble TRAIL is present at extremely high levels in human colostrum and human milk and might have a significant role in mediating the anti-cancer activity of human milk.
Keywords: Adult; Apgar Score; Colostrum; Female; Gestational Age; Humans; Infant Formula; Infant, Newborn; Milk, Human; TNF-Related Apoptosis-Inducing Ligand

Haematopoietic SCT in severe autoimmune diseases: updated guidelines of the European Group for Blood and Marrow Transplantation. - Snowden, J A; Saccardi, R; Allez, M; Ardizzone, S; Arnold, R; Cervera, R; Denton, C; Hawkey, C; Labopin, M; Mancardi, G; Martin, R; Moore, J J; et al. (Bone Marrow Transplant, 2012)
In 1997, the first consensus guidelines for haematopoietic SCT (HSCT) in autoimmune diseases (ADs) were published, while an international coordinated clinical programme was launched. These guidelines provided broad principles for the field over the following decade and were accompanied by comprehensive data collection in the European Group for Blood and Marrow Transplantation (EBMT) AD Registry. Subsequently, retrospective analyses and prospective phase I/II studies generated evidence to support the feasibility, safety and efficacy of HSCT in several types of severe, treatment-resistant ADs, which became the basis for larger-scale phase II and III studies. In parallel, there has also been an era of immense progress in biological therapy in ADs. The aim of this document is to provide revised and updated guidelines for both the current application and future development of HSCT in ADs in relation to the benefits, risks and health economic considerations of other modern treatments. Patient safety considerations are central to guidance on patient selection and HSCT procedural aspects within appropriately experienced and Joint Accreditation Committee of International Society for Cellular Therapy and EBMT accredited centres. A need for prospective interventional and non-interventional studies, where feasible, along with systematic data reporting, in accordance with EBMT policies and procedures, is emphasized.
Keywords: Autoimmune Diseases; Clinical Trials, Phase I as Topic; Clinical Trials, Phase II as Topic; European Union; Female; Hematopoietic Stem Cell Transplantation; Humans; Male; Risk Factors; Safety; Severity of Illness Index

High prevalence of serum antibodies reacting with simian virus 40 capsid protein mimotopes in patients affected by malignant pleural mesothelioma. - Mazzoni, Elisa; Corallini, Alfredo; Cristaudo, Alfonso; Taronna, Angelo; Tassi, Gianfranco; Manfrini, Marco; Comar, Manola; Bovenzi, Massimo; Guaschino, Roberto; Vaniglia, Francesca; Magnani, Corrado; Casali, Ferruccio; et al. (Proc Natl Acad Sci U S A, 2012)
Human malignant pleural mesothelioma (MPM) is considered a rare tumor, but recent estimations indicate that one-quarter million people will die of this neoplasm in Europe in the next three decades. The mineral asbestos is considered the main causative agent of this neoplasm. MPM is largely unresponsive to conventional chemotherapy/radiotherapy. In addition to asbestos exposure, genetic predisposition to asbestos carcinogenesis and to simian virus (SV)40 infection has also been suggested. SV40 is a DNA tumor virus found in some studies to be associated at high prevalence with MPM. SV40 sequences have also been detected, although at a lower prevalence than in MPM, in blood specimens from healthy donors. However, some studies have failed to reveal SV40 footprints in MPM and its association with this neoplasm. These conflicting results indicate the need for further investigations with new approaches. We report on the presence of antibodies in serum samples from patients affected by MPM that specifically react with two different SV40 mimotopes. The two SV40 peptides used in indirect ELISAs correspond to viral capsid proteins. ELISA with the two SV40 mimotopes gave overlapping results. Our data indicate that in serum samples from MPM-affected patients (n = 97), the prevalence of antibodies against SV40 viral capsid protein antigens is significantly higher (26%, P = 0.043) than in the control group (15%) represented by healthy subjects (n = 168) with the same median age (66 y) and sex. Our results suggest that SV40 is associated with a subset of MPM and circulates in humans.
Keywords: Amino Acid Sequence; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mesothelioma; Molecular Sequence Data; Pleural Neoplasms; Pregnancy; Simian virus 40

HIV-1 induces NALP3-inflammasome expression and interleukin-1β secretion in dendritic cells from healthy individuals but not from HIV-positive patients. - Pontillo, Alessandra; Silva, Lais T; Oshiro, Telma M; Finazzo, Claudia; Crovella, Sergio; Duarte, Alberto J S (AIDS, 2012)
OBJECTIVE: NALP3-inflammasome is an innate mechanism, alternative to type-1 interferon, which is able to recognize nucleic acids and viruses in the cytoplasm and to induce pro-inflammatory response. Here, we hypothesized the involvement of inflammasome in the early defense against HIV-1 and in the full maturation of dendritic cells: for this, we evaluated the response of dendritic cells pulsed with HIV-1 in terms of inflammasome activation in healthy donors. Moreover, inflammasome response to HIV was evaluated in HIV-infected individuals. DESIGN AND METHODS: Monocyte-derived dendritic cells isolated from 20 healthy individuals (HC-DC) and 20 HIV-1-infected patients (HIV-DC) were pulsed with alditrithiol-2-inactivated HIV-1. We then analyzed inflammasome genes expression and interleukin-1β (IL-1β) secretion. RESULTS: In HC-DC, HIV-1 induced higher NLRP3/NALP3 mRNA expression compared with other inflammasome genes such as NALP1/NLRP1 or IPAF/NLRC4 (P < 0.001). This augmented expression was accompanied by CASP1-increased and IL1B-increased mRNA levels and by a significant increment of IL-1β secretion (P < 0.05). Otherwise, HIV-1 failed to activate inflammasome and cytokine production in HIV-DC. HIV-DC showed an increased NLRP3/NALP3 basal expression, suggesting a chronic inflammatory profile of patients' immune cells. CONCLUSION: HIV-1 was able to induce a NALP3-inflammasome response in healthy individuals, indicating that this inflammasome could play a role in the first steps of HIV-1 infection; the consequent inflammatory process may be important for directing host immune response against the virus and/or disease progression. HIV-DC seemed to be chronically activated, but unresponsive against pathogens. Our findings could be of interest considering the ongoing research about dendritic cell manipulation and therapeutic strategies for AIDS involving dendritic cell-based immune-vaccines.
Keywords: Acquired Immunodeficiency Syndrome; Adult; Brazil; Carrier Proteins; Caspase 1; Cells, Cultured; Dendritic Cells; DNA, Viral; Female; HIV-1; Humans; Immunity, Innate; Inflammasomes; Interleukin-1beta; Male; Tumor Necrosis Factor-alpha

HLA-G 14bp del/ins genetic variation: association with susceptibility to human immunodeficiency virus-1 vertical transmission but not with human immunodeficiency virus-1 infection through horizontal transmission. - Segat, L; Crovella, S (Tissue Antigens, 2012)
Keywords: Ethnic Groups; Genetic Association Studies; Genetic Predisposition to Disease; HIV Infections; HIV-1; HLA-G Antigens; Humans; INDEL Mutation; Infectious Disease Transmission, Vertical; Polymorphism, Genetic

How the newly introduced compression, airway, and breathing sequence affects the training in pediatric cardiopulmonary resuscitation. - Lubrano, Riccardo; Messi, Gianni; Elli, Marco (Am J Emerg Med, 2012)
Keywords: Cardiopulmonary Resuscitation; Clinical Competence; Feedback; Female; Heart Massage; Humans; Inservice Training; Male

Hydrogen sulfide down-regulates the expression and release of osteoprotegerin (OPG) by vascular endothelial cells. - Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Celeghini, Claudio; Secchiero, Paola; Zauli, Giorgio (Invest New Drugs, 2012)
Keywords: Cell Death; Cytostatic Agents; Down-Regulation; Human Umbilical Vein Endothelial Cells; Humans; Hydrogen Sulfide; Osteoprotegerin; Tumor Necrosis Factor-alpha

Hearing function and thresholds: a genome-wide association study in European isolated populations identifies new loci and pathways. - Girotto, Giorgia; Pirastu, Nicola; Sorice, Rossella; Biino, Ginevra; Campbell, Harry; d'Adamo, Adamo P; Hastie, Nicholas D; Nutile, Teresa; Polasek, Ozren; Portas, Laura; Rudan, Igor; Ulivi, Sheila; et al. (J Med Genet, 2011)
BACKGROUND: Hearing is a complex trait, but until now only a few genes are known to contribute to variability of this process. In order to discover genes and pathways that underlie auditory function, a genome-wide association study was carried out within the International Consortium G-EAR. METHODS: Meta-analysis of genome-wide association study's data from six isolated populations of European ancestry for an overall number of 3417 individuals. RESULTS: Eight suggestive significant loci (p<10(-7)) were detected with a series of genes expressed within the inner ear such as: DCLK1, PTPRD, GRM8, CMIP. Additional biological candidates marked by a single nucleotide polymorphism (SNP) with a suggestive association (p<10(-6)) were identified, as well as loci encompassing 'gene desert regions'-genes of unknown function or genes whose function has not be linked to hearing so far. Some of these new loci map to already known hereditary hearing loss loci whose genes still need to be identified. Data have also been used to construct a highly significant 'in silico' pathway for hearing function characterised by a network of 49 genes, 34 of which are certainly expressed in the ear. CONCLUSION: These results provide new insights into the molecular basis of hearing function and may suggest new targets for hearing impairment treatment and prevention.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Auditory Threshold; Carrier Proteins; Databases, Genetic; Europe; European Continental Ancestry Group; Female; Founder Effect; Genetic Linkage; Genome-Wide Association Study; Hearing; Hearing Loss; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice; Phenotype; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Receptor-Like Protein Tyrosine Phosphatases, Class 2; Receptors, Metabotropic Glutamate

High incidence of NLRP3 somatic mosaicism in patients with chronic infantile neurologic, cutaneous, articular syndrome: results of an International Multicenter Collaborative Study. - Tanaka, Naoko; Izawa, Kazushi; Saito, Megumu K; Sakuma, Mio; Oshima, Koichi; Ohara, Osamu; Nishikomori, Ryuta; Morimoto, Takeshi; Kambe, Naotomo; Goldbach-Mansky, Raphaela; Aksentijevich, Ivona; de Saint Basile, Geneviève; et al. (Arthritis Rheum, 2011)
OBJECTIVE: Chronic infantile neurologic, cutaneous, articular (CINCA) syndrome, also known as neonatal-onset multisystem inflammatory disease (NOMID), is a dominantly inherited systemic autoinflammatory disease. Although heterozygous germline gain-of-function NLRP3 mutations are a known cause of this disease, conventional genetic analyses fail to detect disease-causing mutations in ∼40% of patients. Since somatic NLRP3 mosaicism has been detected in several mutation-negative NOMID/CINCA syndrome patients, we undertook this study to determine the precise contribution of somatic NLRP3 mosaicism to the etiology of NOMID/CINCA syndrome. METHODS: An international case-control study was performed to detect somatic NLRP3 mosaicism in NOMID/CINCA syndrome patients who had shown no mutation during conventional sequencing. Subcloning and sequencing of NLRP3 was performed in these mutation-negative NOMID/CINCA syndrome patients and their healthy relatives. Clinical features were analyzed to identify potential genotype-phenotype associations. RESULTS: Somatic NLRP3 mosaicism was identified in 18 of the 26 patients (69.2%). Estimates of the level of mosaicism ranged from 4.2% to 35.8% (mean ± SD 12.1 ± 7.9%). Mosaicism was not detected in any of the 19 healthy relatives (18 of 26 patients versus 0 of 19 relatives; P < 0.0001). In vitro functional assays indicated that the detected somatic NLRP3 mutations had disease-causing functional effects. No differences in NLRP3 mosaicism were detected between different cell lineages. Among nondescript clinical features, a lower incidence of mental retardation was noted in patients with somatic mosaicism. Genotype-matched comparison confirmed that patients with somatic NLRP3 mosaicism presented with milder neurologic symptoms. CONCLUSION: Somatic NLRP3 mutations were identified in 69.2% of patients with mutation-negative NOMID/CINCA syndrome. This indicates that somatic NLRP3 mosaicism is a major cause of NOMID/CINCA syndrome.
Keywords: Adolescent; Adult; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Genetic Association Studies; Humans; Infant; Male; Mosaicism

High prevalence of BK polyomavirus sequences in human papillomavirus-16-positive precancerous cervical lesions. - Comar, Manola; Bonifacio, Daniela; Zanconati, Fabrizio; Di Napoli, Michela; Isidoro, Erica; Martini, Fernanda; Torelli, Lucio; Tognon, Mauro (J Med Virol, 2011)
High- and low-grade cervical lesions were analyzed for the presence of polyomavirus (PYV) and human papillomavirus (HPV) sequences. In precancerous cervical lesions, the overall prevalence of PYV sequences was 44% (41/93). Specifically, among the PYV-positive samples, 83% (34/41) tested positive for BK polyomavirus (BKV) sequences, whereas 17% (7/41) were positive for JC-virus. None of the samples were positive for simian virus 40. The presence of BKV DNA in high-grade squamous intraepithelial lesions was confirmed by in situ PCR. BKV sequences were detected more frequently in high-grade squamous intraepithelial lesions, together with the genotype HPV-16. The association of BKV with precancerous cervical lesions suggests that this polyomavirus participates with HPV-16 in the cell transformation process. Alternatively, BKV might multiply better in HPV-16-positive cells from precancerous cervical lesions than in HPV-16-negative cells.
Keywords: Adult; BK Virus; Cervical Intraepithelial Neoplasia; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; JC Virus; Middle Aged; Oncogene Proteins, Viral; Papillomavirus Infections; Precancerous Conditions; Simian virus 40; Uterine Cervical Diseases

High-throughput genotyping robot-assisted method for mutation detection in patients with hypertrophic cardiomyopathy. - Bortot, Barbara; Athanasakis, Emmanouil; Brun, Francesca; Rizzotti, Diego; Mestroni, Luisa; Sinagra, Gianfranco; Severini, Giovanni Maria (Diagn Mol Pathol, 2011)
Hypertrophic cardiomyopathy (HCM) is the most frequent autosomal dominant genetic heart muscle disease and the most common cause of sudden cardiac death in young people (under 30 y of age), who are often unaware of their underlying condition. Genetic screening is now considered a fundamental tool for clinical management of HCM families. However, the high genetic heterogeneity of HCM makes genetic screening very expensive. Here, we propose a new high-throughput genotyping method based on a HCM 96-well sequencing plate for the analysis of 8 of the most frequent HCM-causing sarcomeric genes by automating several processes required for direct sequencing, using a commercially available robotic systems and routinely used instruments. To assess the efficiency of the robot-assisted method, we have analyzed the entire coding sequence and flanking intronic sequences of the 8 sarcomeric genes in samples from 18 patients affected by HCM and their relatives, which revealed 9 different mutations, 3 of which were novel. The automated, robot-assisted assembling of polymerase chain reaction, purification of polymerase chain reaction products, and assembly of sequencing reactions resulted in a substantial saving of time, reagent costs, and reduction of human errors, and can therefore be proposed as a primary strategy for mutation identification in HCM genetic screening in many medical genetic laboratories.
Keywords: Cardiomyopathy, Hypertrophic; DNA Mutational Analysis; Genetic Predisposition to Disease; Genetic Testing; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Muscle Proteins; Mutation; Robotics

HLA-G 14 bp deletion/insertion polymorphism in celiac disease. - Fabris, Annalisa; Segat, Ludovica; Catamo, Eulalia; Morgutti, Marcello; Vendramin, Anna; Crovella, Sergio (Am J Gastroenterol, 2011)
OBJECTIVES: Nonclassical major histocompatibility class I HLA-G antigen is a tolerogenic molecule that inhibits lytic activity of natural killer (NK) cells and cytotoxic T lymphocytes. Because of its immunomodulatory and tolerogenic properties, HLA-G molecules may have a role in celiac disease (CD). We analyzed the HLA-G 14 bp deletion/insertion polymorphism, known to have a functional effect on mRNA stability, in a group of 522 CD patients, stratified for the presence of HLA-DQ2 genotype, and 400 healthy individuals to evaluate the possible effect of the polymorphism on the risk to develop the disease. METHODS: HLA-G 14 bp deletion/insertion polymorphism (rs1704) was detected by polymerase chain reaction and double-checked by direct sequencing. RESULTS: The 14 bp inserted (I) allele and the homozygous I/I genotype were significantly more frequent in CD patients than in healthy controls. The presence of I allele was associated with an increased risk of CD (OR 1.35) and the effect of I allele was consistent with a recessive genetic model (P<0.001). CONCLUSIONS: Our results also indicate that the effect of the HLA-G D/I polymorphism is restricted for HLA-DQ2, and not simply due to the presence of linkage disequilibrium with the major known risk factor; moreover we found that the presence of the I allele confers an increased risk of CD in addition to the risk conferred by HLA-DQ2 alone and that subjects that carry both DQ2 and HLA-G I alleles have an increased risk of CD than subjects that carry DQ2 but not the I allele.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Celiac Disease; Child; Child, Preschool; Confidence Intervals; Female; Genetic Predisposition to Disease; Genotype; Histocompatibility Antigens Class I; HLA Antigens; HLA-DQ Antigens; HLA-G Antigens; Humans; Male; Middle Aged; Mutagenesis, Insertional; Odds Ratio; Polymerase Chain Reaction; Polymorphism, Genetic; Reference Values; RNA Stability; Sequence Deletion; Young Adult

Horizontal gaze palsy and progressive scoliosis without ROBO3 mutations. - Abu-Amero, Khaled K; Faletra, Flavio; Gasparini, Paolo; Parentin, Fulvio; Pensiero, Stefano; Alorainy, Ibrahim A; Hellani, Ali M; Catalano, Dario; Bosley, Thomas M (Ophthalmic Genet, 2011)
BACKGROUND: To describe clinical and genetic observations in a patient with horizontal gaze palsy and progressive scoliosis (HGPPS) without identified mutations in the ROBO3 gene. MATERIALS AND METHODS: Neurologic and orthopedic evaluation of the proband; sequencing all exons, exon-intron boundaries, and promoter region of ROBO3 in the proband and his mother. Array CGH was also carried out in the proband and his mother to evaluate possible chromosomal deletion(s) and/or duplication(s). RESULTS: The proband had complete horizontal gaze restriction with full vertical gaze and small amplitude horizontal pendular nystagmus. He also had severe scoliosis and brainstem hypoplasia pathognomonic of HGPPS. However, complete sequencing of ROBO3 twice in both forward and reverse directions did not reveal any mutations. Array CGH investigation revealed no chromosomal abnormalities. CONCLUSIONS: This patient had clinical and neuroimaging characteristics considered pathognomonic of HGPPS and yet did not have ROBO3 mutations. A clinical misdiagnosis is unlikely in the absence of facial weakness (typical of Moebius syndrome), deafness (typical of the HOXA1 spectrum), or mental retardation (typical of other central decussation abnormalities). It is perhaps more likely that a phenotype identical to HGPPS can be caused by abnormalities in ROBO3 splice variant expression, by mutations of a gene other than ROBO3, or by some environmental or epigenetic factor(s) inhibiting the action of ROBO3 or its protein product in the developing brainstem.
Keywords: Child; Humans; Kyphosis; Magnetic Resonance Imaging; Male; Mutation; Ocular Motility Disorders; Oculomotor Nerve Diseases; Pedigree; Receptors, Immunologic; Scoliosis

Hepatic glycogenosis in an adolescent with diabetes. - Bua, Jenny; Marchetti, Federico; Faleschini, Elena; Ventura, Alessandro; Bussani, Rossana (J Pediatr, 2010)
Keywords: Adolescent; Diabetes Mellitus, Type 1; Female; Glycogen Storage Disease; Humans; Liver Diseases

High polymorphism of the MBL2 gene in patients with atopic dermatitis. - Carréra, Matilde Campos; Moura, Patrícia; Crovella, Sergio; de Souza, Paulo Roberto Eleutério; de Alencar, Luiz Cláudio Arraes; Sarinho, Emanuel (Ann Allergy Asthma Immunol, 2010)
BACKGROUND: Low serum levels of mannose-binding lectin (MBL) are determined mainly by variant alleles of the MBL2 gene and it has been suggested that MBL may play a role in the susceptibility to atopic dermatitis (AD). OBJECTIVE: The aim was to investigate the difference of the frequency of MBL2 variant alleles in AD patients and in a group of individuals without AD, and associate the MBL2 alleles with AD severity. METHODS: MBL2 variant allele's frequency was investigated in 131 children with AD and 165 healthy children/adolescents matched by convenience. The severity of disease was graded according to the SCORing Atopic Dermatitis (SCORAD) index. The first exon variants were called "O" and the wild type "A". The variants in the promoter were H/L at -550 and X/Y at -221, determined by Real Time PCR. RESULTS: Children with AD had higher frequency of allele O and the genotypes related to low or deficient levels of MBL, when compared to the healthy group (p = 0.0012 and p < 0.001, respectively), but not with AD severity. CONCLUSION: Low or deficient MBL serum levels determined genetically may contribute to the predisposition for AD, but not for disease severity.
Keywords: Adolescent; Alleles; Child; Child, Preschool; Dermatitis, Atopic; Disease Progression; Female; Genetic Predisposition to Disease; Genotype; Humans; Infant; Male; Mannose-Binding Lectin; Polymorphism, Genetic; Promoter Regions, Genetic

Histatins in non-human primates: gene variations and functional effects. - Padovan, Lara; Segat, Ludovica; Pontillo, Alessandra; Antcheva, Nikolinka; Tossi, Alessandro; Crovella, Sergio (Protein Pept Lett, 2010)
Human histatins are histidine-rich, low molecular weight salivary proteins that contribute to the immune system of the oral cavity. In this work, nucleotide sequences of the HIS1 (coding for histatin 1) and HIS2 (coding for histatin 3) genes, homologous to the human ones, have been sequenced and analysed in five primates species including Great Ape, Hylobatidae and Cercopithecidae. In HIS1, the region corresponding to the putative mature peptide shows a premature stop codon in Macaca and Cercopithecus, while HIS2 a six codon insertion in the Cercopithecidae. Histatin 5, a 24-residue peptide derived from histatin 3, is the most antimicrobially active among human histatins, thus macaque and nomascus orthologues of histatin 5 were selected for chemical synthesis and functional characterization, in comparison to the human peptide. All synthesized histatins are predicted to be poorly amphipathic, depending on the charged state of His residues and assume partially a-helical conformations only in lipophilic conditions. Antimicrobial assays against Candida and Criptococcus spp. indicate somewhat different spectra of in vitro activity against the tested fungi. We have described HIS1 and HIS2 gene variations in primates and have analysed their functional effects on selected Hst5 orthologues. The human antimicrobial peptide has been proposed to represent an important lead for new generation of antimicrobial compounds for the treatment of oral mycoses, thus the information from the non-human primates histatins studied may aid strategies for drugs design.
Keywords: Amino Acid Sequence; Animals; Anti-Infective Agents; Base Sequence; Candida; Catarrhini; Cell Proliferation; Computational Biology; Cryptococcus; Genetic Variation; Histatins; Humans; Molecular Sequence Data; Phylogeny; Sequence Alignment; Sequence Analysis, DNA

HLA-G*0105N allele is associated with augmented risk for HIV infection in white female patients. - Segat, Ludovica; Catamo, Eulalia; Fabris, Annalisa; Morgutti, Marcello; D'Agaro, Pierlanfranco; Campello, Cesare; Crovella, Sergio (AIDS, 2010)
We analyzed HLA-G 3777G > C, HLA-G 14 bp deletion/insertion and HLA-G*0105N polymorphisms in HIV-positive white adult participants, infected through horizontal heterosexual transmission, and unexposed uninfected individuals, all from north eastern Italy. We report a new association between the HLA-G*0105N allele and HIV infection in adult white female participants, being HLA-G*0105N null allele correlated with an augmented risk (odds ratio = 4.35, 95% confidence interval = 1.38-18.07, P = 0.005) for HIV infection.
Keywords: Adolescent; Adult; Aged; Female; Genetic Predisposition to Disease; Histocompatibility Antigens Class I; HIV Infections; HIV-1; Humans; Middle Aged; Polymorphism, Genetic; Young Adult

Hot water and preparation of infant formula: how hot does it have to be to be safe? - Davanzo, Riccardo; Giurici, Nagua; Demarini, Sergio (J Pediatr Gastroenterol Nutr, 2010)
Keywords: Guidelines as Topic; Hot Temperature; Humans; Infant; Infant Formula; Water; World Health Organization

[Human papillomavirus cervical infection: viral genotyping and risk factors for high-grade squamous intraepithelial lesion and cervix cancer]. - de Mendonça, Vilma Guimarães; Guimarães, Maria José Bezerra; de Lima Filho, José Luiz; de Mendonça, Carolina Guimarães; Martins, Danyelly Bruneska Gondim; Crovella, Sergio; de Alencar, Luiz Cláudio Arraes (Rev Bras Ginecol Obstet, 2010)
PURPOSE: to analyze the characteristics of viral infection and the risk factors for high-grade squamous intraepithelial lesion and cervical carcinoma in women with cervical HPV infection. METHODS: a case-control study was conducted on women with cervical HPV at a Gynecology reference service enrolled at the Public Health System, located in Recife, Northeastern Brazil. The groups of cases (72 women with high-grade squamous intraepithelial lesion or cervical cancer) and controls (176 women with normal Pap smear or benign alterations) were investigated for six viral genotypes (HPV 16, 18, 31, 33, 6, 11) in ecto- and endocervical material using MY09/MY11 primers. The independent variables were ranked in three levels of determination: distal (sociodemographic), intermediate (behavioral) and proximal (previous Pap smear). The homogeneity of proportions was tested (χ2), unadjusted Odds Ratios (OR) were obtained and hierarchical logistic regression was applied to the final model, with adjustment of the effect of each variable to the outcome based on the variables in the same and previous levels of causality. RESULTS: the viral genotype of cervical infection was identified in 76.6% of the 248 women participating in the study. High-risk HPV genotypes (83.4% of cases and 67.1% of controls) were predominant, especially HPV 16 and 31. The distal risk factors identified were: living in a rural area (OR=2.71, 95%CI: 1.18-6.23), less than three years of study (OR=3.97, 95%CI: 2.09-7.54) and family income below two minimum wages (OR=3.30, 95%CI: 1.04-10.51); intermediate: four or more pregnancies (OR=2.00, 95%CI: 1.06-3.76); and proximal: absence of a previous Pap smear (OR=9.74, 95%CI: 2.48-38.28). CONCLUSIONS: genotypes 16 and 31 of cervical HPV infection are predominant among women assisted by the Public Health System in Northeastern Brazil. Socioeconomic and reproductive factors, as well as the absence of cytological screening, represent risk factors for the progression of infection to high-grade squamous intraepithelial lesion and cervical cancer.
Keywords: Adult; Carcinoma in Situ; Case-Control Studies; Female; Genotype; Humans; Papillomaviridae; Papillomavirus Infections; Risk Factors; Socioeconomic Factors; Uterine Cervical Neoplasms